1988
DOI: 10.1179/bjo.15.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Cephalometric Measurements

Abstract: This cephalometric study was undertaken to compare and contrast the errors involved in taking linear and angular measurements using three different methods; hand instruments on tracing, digitization of tracings, and direct digitization of the radiographs. Of the three methods direct digitization of the radiographs proved to be the most reproducible particularly with angular measurements, although statistically significant differences were rarely found. Tracings were advantageous only with linear measurements i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
44
0
31

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 5 publications
6
44
0
31
Order By: Relevance
“…However, as to the anterior inferior facial height, the discrepancy was evident ( figure 2A), showing statistically significantly more improvement in response to treatment with the appliances, as occurred in other studies 1,12,13,18,21,22,25 . This behavior was followed by the corresponding tegument facial height (figure 2B), thus with larger values, probably because of the major nasal base stability in comparison with the anterior nasal spine.…”
supporting
confidence: 69%
See 2 more Smart Citations
“…However, as to the anterior inferior facial height, the discrepancy was evident ( figure 2A), showing statistically significantly more improvement in response to treatment with the appliances, as occurred in other studies 1,12,13,18,21,22,25 . This behavior was followed by the corresponding tegument facial height (figure 2B), thus with larger values, probably because of the major nasal base stability in comparison with the anterior nasal spine.…”
supporting
confidence: 69%
“…Like Houston 16 and Sandler 25 stated, errors smaller than 1.5 o or 1mm are not clinically important. Analyses of the reliability of the cephalometric tracing method used demonstrated that the difference was significant only for three variables, showing good reproducibility, and the analyses of variance could not find statistical differences between the initial values of the three groups, except for one variable.…”
Section: Methodology Reliabilitymentioning
confidence: 88%
See 1 more Smart Citation
“…5,7,13,17,20,21,23 Its accuracy depends on the anatomical structure used, the radiographic image quality, visual acuity and experience of the operator on locating the landmarks, considering that great care must be taken so that measurement errors do not influence the study. 5,7 In order to avoid the incorporation of errors in the identification of landmarks, we chose to fixate 1-mm radiopaque spheres in selected regions of the dry skull.…”
Section: E6mentioning
confidence: 99%
“…Traditional cephalometric analysis performed by tracing radiographic landmarks on acetate overlays and measuring with the use of protractor is very time consuming and has several drawbacks, including a high risk of errors during hand tracing, landmark identification and measurement. 1,2 Cephalometric errors can be divided into acquisition, identification and technical measurement errors. Research carried out on conventional cephalometrics proved landmark identification to be the main source of error.…”
Section: Introductionmentioning
confidence: 99%